PENGEMBANGAN LIFE SKILLS SANTRI DI PONDOK PESANTREN AL MUMTAZ JAYANTI TANGERANG - Mumu Zainal Mutaqin Zainal Mutaqin (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2023)
This study aims to explore the Al Mumtaz Islamic boarding school which focuses on the life skills of the students, namely the students' ability to speak Arabic and English. This is stated in the vision of Islamic boarding schools to prepare a generation of quality Muslims with a learning process approach. This study uses a qualitative research method with a type of descriptive research intended to understand the phenomenon of what is experienced by research subjects, for example behavior, perceptions, motivations, actions, etc., holistically and by means of descriptions in the form of words and language in a particular context. naturally and by utilizing various natural methods. Al Mumtaz Islamic Boarding School in improving the life skills of students in Arabic and English, including. First, personal skills through a program of routine recitation of books, this activity is carried out routinely at dawn. Second, social skills through organizations in the field of language. Third, academic skills through educational programs, namely the Santri scientific forum. Fourth, vocational skills through language extracurricular activities. In addition, one of the supporting and inhibiting factors is the extracurriculars that are applied in Islamic boarding schools to support and add insight to students. While the inhibiting factors, the persistence of means and motivation within the students